Pengaruh Media Sosial, Promosi Penjualan dan Kepuasan Pelanggan terhadap Keputusan Pembelian Berulang melalui Experience sebagai Variabel Mediasi di Restaurant The Champlung Seminyak - Putra, I Putu Noval Adi Suarsa; Gorda, AAA. Ngurah Sri Rahayu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Consumer behavior in the restaurant industry is increasingly shaped by customer satisfaction, sales promotions, and social media, reflecting the significant changes brought about by the rapid development of digital media in marketing strategies. Repeat purchase decisions at The Champlung Restaurant Seminyak are investigated by assessing how social media, sales promotions, and customer satisfaction exert their influence through customer experience as a mediating factor. Data were obtained through structured questionnaires administered to 114 customers who had previously dined at the restaurant, and these data were analyzed using a quantitative explanatory research approach. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4. Unlike sales promotion, which fails to show a significant impact, social media is proven to positively and significantly influence repeat purchase decisions. Repeat purchase decisions are significantly affected by customer experience, which in turn is strongly shaped by customer satisfaction. The effects of social media and sales promotion are not mediated by customer experience; instead, customer experience serves as a mediator only in the relationship between customer satisfaction and repeat purchase decisions. These findings suggest that repeat purchase behavior in the restaurant sector is more strongly driven by satisfaction and memorable dining experiences than by short-term promotional incentives.